Mechanisms of Implementation of e-Bupot Applications in The Fulfillment Taxation Obligations of PPh 23 and PPN - Mulyanah, Mulyanah; Pratiwi, Refi; Aulia, Ratna Wulan (PT. EQUATOR SINAR AKADEMIA, 2024)
Mechanism for Implementing the E-Bupot Application in Fulfilling the Implementation of Income Tax Article 23 and VAT Tax Obligations at the Banten Province Youth and Sports Service. The purpose of this writing is: (1). To find out the mechanism for implementing the E-Bupot PPh Article 23 and VAT application at the Banten Province Youth and Sports Service. (2). To find out the obstacles that often occur in the process of implementing the E-Bupot application for PPh article 23 and VAT. The method used in this writing is the descriptive method, while the techniques used in the data collection process are observation, interviews and documentation methods. The results of this writing show that: (1). The Banten Province Youth and Sports Service in carrying out the preparation of proof of withholding of PPh article 23 and VAT is in accordance with applicable regulations, namely the Directorate General of Taxes Regulation Number PER-24/PJ/2021 concerning the form and procedures for making Proof of Withholding or Collection of Unified Tax. (2). The obstacles that often occur in reporting Proof of Withholding or Collection at the Banten Province Youth and Sports Service can be resolved except when inputting the tax period which does not match the tax period that must be reported.